Pengaruh Variasi Latihan Core Terhadap Kemampuan Balance dan Forehand Drive Atlet Putra - Hidayah NST, M. Wahyu; Siahaan, David (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to determine the impact of core training variations on balance and forehand drive abilities in male athletes of the Unimed Tennis Community in 2023. It addresses the issue of inadequate balance when chasing the ball, leading to hitting errors such as balls getting caught in the net, improper racket-ball contact, lack of control, and shots going out of bounds.Method – The research employed an experimental method with a one-group pre-test and post-test design. The study was conducted at the Unimed tennis court, with a purposive sampling technique selecting six male athletes who met the study criteria. Data were collected through pre-test and post-test assessments of balance and forehand drive performance, with the results analyzed using t-tests to determine the effectiveness of core training variations. Findings – The results showed a significant effect of core training variations on the athletes' balance and forehand drive abilities. The analysis revealed a t-value of 16.813 for balance and 13.636 for forehand drive, both exceeding the critical t-value of 2.015. These findings indicate that core training variations positively influenced both balance and forehand drive performance in male athletes of the Unimed Tennis Community. Research Implications – The study highlights the importance of incorporating core training variations in athletic training programs to improve balance and forehand drive skills. Coaches and sports trainers are encouraged to implement these exercises to enhance performance and reduce errors during play. Future research could explore the long-term effects of core training variations and their impact on other tennis skills or different athlete populations.